A Thermodynamic and Kinetic Evaluation of the Adsorption of Pb(II) Ions Using Peanut (Arachis Hypogaea) Shell-Based Biochar from Aqueous Media - Tasar, Seyda; Ozer, Ahmet (Hard, 2020)
In this study, biochar from peanut shells was used to remove Pb(II) ions from aqueous media using a batch method. Adsorption studies were conducted to optimize the adsorption parameters, such as contact time, the initial pH of aqueous media, temperature, initial concentration of lead ions, and the dosage of biochar. The optimum adsorption conditions were found to be contact time: 180 min, initial pH of aqueous media: 5.5 0.02, temperature: 293 K, initial concentration of lead ions: 100 ppm, and the dosage of biochar: 2 g/L. The adsorption yield of Pb(II) ions on the biochar was found to be 89% under these conditions. The experimental results were evaluated by applying the Langmuir, Freundlich, Temkin, and Dubinin-Radushkevich (D-R) isotherm models. We found that the Langmuir isotherm describe the adsorption data very well. The theoretical maximum adsorption capacity (q(c)) was determined as 56.5 mg/g using the Langmuir isotherm. In the concept of the research, kinetic investigations also were conducted. Pseudo first-order, pseudo second-order, intraparticle diffusion, and Endovich kinetic models were used to calculate the kinetic parameters and determine the ideal mechanism of the adsorption process. It was found that the pseudo second-order model could be used to explain the experimental data. The adsorption was a controlled chemisorption mechanism. The thermodynamic parameters (Delta H degrees, Delta S degrees, and Delta G degrees) were calculated using basic thermodynamic equations, and they indicated that the adsorption process was spontaneous at all temperatures and that the process was exothermic. Consequently, it was concluded that the peanut shell-based biochar can be used as a suitable and economical adsorbent for the removal of Pb(II) ions from aqueous media.
Keywords: adsorption; Pb(II) ions; biochar; FTIR-SEM; thermodynamic and kinetic evaluation